Physician stress and burnout: the impact of health information technology. (5th December 2018) - Gardner, Rebekah L; Cooper, Emily; Haskell, Jacqueline; Harris, Daniel A; Poplau, Sara; Kroth, Philip J; Linzer, Mark
Abstract: Objective: To quantify how stress related to use of health information technology (HIT) predicts burnout among physicians. Methods: All 4197 practicing physicians in Rhode Island were surveyed in 2017 on their HIT use. Our main outcome was self-reported burnout. The presence of HIT-related stress was defined by report of at least 1 of the following: poor/marginal time for documentation, moderately high/excessive time spent on the electronic health record (EHR) at home, and agreement that using an EHR adds to daily frustration. We used logistic regression to assess the association between each HIT-related stress measure and burnout, adjusting for respondent demographics, practice characteristics, and the other stress measures. Results: Of the 1792 physician respondents (43% response rate), 26% reported burnout. Among EHR users (91%), 70% reported HIT-related stress, with the highest prevalence in primary care-oriented specialties. After adjustment, physicians reporting poor/marginal time for documentation had 2.8 times the odds of burnout (95% CI: 2.0–4.1; P  < .0001), compared to those reporting sufficient time. Physicians reporting moderately high/excessive time on EHRs at home had 1.9 times the odds of burnout (95% CI: 1.4–2.8; P  < .0001), compared to those with minimal/no EHR use at home. Those who agreed that EHRs add to their daily frustration had 2.4 times the odds of burnout (95% CI: 1.6–3.7; P  < .0001), compared to those who disagreed. Conclusion: HIT-related stress is measurable, common (about 70% among respondents), specialty-related, and independently predictive of burnout symptoms. Identifying HIT-specific factors associated with burnout may guide healthcare organizations seeking to measure and remediate burnout among their physicians and staff.